Variable-temperature time-resolved emission spectra studies of random pyrene urethane methacrylate copolymers with high pyrene incorporation - Kaushlendra, K.; Asha, S. K. (Journal of Physical Chemistry B, 2013)
A series of random co-polyurethane methacrylate comb polymers with pyrene (Py) and 3-pentadecylphenol (PDP) as pendant units Were prepared by free radical polymerization. The pyrene labeling was varied from 1 to 100 mol %. The excimer emission of these copolymers were studied as a function of both time and temperature using time-resolved emission spectra (TRES) experiments and variable-temperature steady-state fluorescence measurements. Variable-temperature steady-state as well as decay experiments showed that the contribution from excimers via diffusional encounters increased at the cost of pyrene monomer as the temperature increased until similar to 50 degrees C; beyond which nonradiative losses predominated. TRES collected at 25 and 70 degrees C were compared to study the nature and origin of emitting species as a function of pyrene loading. TRES at 25 degrees C dearly indicated the presence of ground state pyrene dimers with emission centered at similar to 435 nm which soon gave way to emission centered around 465 and 485 nm in the time gated spectra collected at higher time intervals. In TRES collected at 70 degrees C, excimer emission centered at 465 and 485 nm was very high even at short time scales. The lowest pyrene loaded polymer PIHPDP-1Py did not exhibit excimer emission in the TRES collected at 25 degrees C as well as 70 degrees C.